PERILAKU AWARENESS SISWA KELAS V SD DALAM MEMBACA PEMAHAMAN TEKS NONFIKSI - Mikhael Klemens Kedang; Blandina Seko Bani (Universitas Negeri Surabaya, 2021)
The purpose of this study was to describe awareness behavior using a descriptive-qualitative approach in the first semester of class VA and VB, with a total of 30 students (16 boys and 14 girls). The data collection process was given a reading comprehension test (TMP), a behavioral awareness test (TPA) 1 which was seen from the test scores of Indonesian Language Subjects for each student. The results of the analysis of TMP, TPA 1, TPA 2 and the Indonesian language test scores were categorized into three abilities, namely high, medium, and low abilities. The three categories are represented by a communicative subject. It was concluded that the SBT awareness behavior in reading comprehension of non-fiction texts fulfilled the five indicators, namely P1, P2, P3, P4 and E1. SBS also fulfills the five indicators, but in implementation there are still errors in the P2 and P3 indicators so that they affect the answers. The SBR ignores indicators P4 and E1, and is less than optimal and does not understand indicators P1, P2, and P3.Keywords: behavior awareness, non-fictional, text reading comprehensionABSTRAK Tujuan penelitian ini adalah mendeskripsikan perilaku awareness menggunakan pendekatan deskriptif-kualitatif di kelas VA dan VB semester I, dengan jumlah kesuluruhan siswa 30 orang (16 laki-laki dan 14 perempuan). Proses pengambilan data diberikan tes membaca pemahaman (TMP), tes perilaku awareness (TPA) 1 yang dilihat dari nilai ulangan Mata Pelajaran Bahasa Indonesia tiap siswa. Hasil analisis TMP, TPA 1, TPA 2 dan nilai ulangan Bahasa Indonesia dikategorikan dalam tiga kemampuan, yakni kemampuan tinggi, sedang, dan rendah. Ketiga kategori itu diwakili salah satu subjek yang komunikatif. Disimpulkan bahwa perilaku awareness SBT dalam membaca pemahaman teks nonfiksi memenuhi kelima indikator, yakni P1, P2, P3, P4 dan E1. SBS juga memenuhi kelima indikator, namun dalam implementasi masih terdapat kekeliruan pada indikator P2 dan P3 sehingga berpengaruh pada jawaban. Adapun SBR yang mengabaikan indikator P4 dan E1, serta kurang maksimal dan kurang paham dalam indikator P1, P2, dan P3.Kata Kunci: kesadaran perilaku, nonfiksi, pemahaman membaca teks